A Pharmacokinetic Study Comparing Eslicarbazepine Acetate Administered Orally as a Crushed or Intact Tablet in Healthy Volunteers. Issue 4 (8th February 2016) - Sunkaraneni, Soujanya; Kharidia, Jahnavi; Schutz, Ralph; Blum, David; Cheng, Hailong
Abstract: The relative bioequivalence of crushed versus intact eslicarbazepine acetate (ESL) tablets (800 mg) administered orally in healthy adults was evaluated in an open‐label, randomized, 2‐period crossover study with a 5‐day washout between treatments. Sample blood levels of eslicarbazepine and (R)‐licarbazepine were determined; pharmacokinetic parameters were derived for eslicarbazepine. Bioequivalence was established if the 90% confidence intervals (CIs) for the geometric mean treatment ratios of eslicarbazepine AUC(0–∞) and Cmax were within the prespecified 80%–125% range. Twenty‐seven subjects in the intent‐to‐treat population (n = 28) completed both treatment periods. Eslicarbazepine exposure measures were similar for crushed versus intact ESL tablets: average Cmax, 11 700 versus 11 500 ng/mL; AUC(0–∞), 225 000 versus 234 000 ng·h/mL; AUC(0–last), 222 000 versus 231 000 ng·h/mL, respectively. Geometric least squares mean ratios (90%CIs) comparing eslicarbazepine exposure measures were within the 80%–125% range (Cmax, 102.63% [97.07%–108.51%]; AUC(0–∞), 96.72% [94.36%–99.13%]; AUC0–last, 96.69% [94.24%–99.21%]). In conclusion, ESL administered orally as a crushed tablet sprinkled on applesauce, or intact were bioequivalent in healthy subjects. Eslicarbazepine bioavailability was not significantly altered by crushing, indicating that ESL tablets can be administered intact or crushed.